Transborder Data Flow in the Developing World: A Question of Balance - Carrie L. Shipley (Journal of Applied Communications, 1984)
This paper is a brief attempt to summarize the possible causes and Circumstances surrounding the controversy over "transborder data flows" (TDF), a controversy which eventually will involve many international communicators.